Two decades of epidemiological surveillance of congenital syphilis in Brazil: concerning the case definitions - Tayra, Ângela; Matida, Luiza H; Saraceni, Valéria; Paz, Leidijany C; Ramos Jr., Alberto N (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: the process of case definition represents an important strategy of epidemiological surveillance to follow important diseases and events for public health. Moreover, it allows the description of occurrence, besides the registry and control strategies’ evaluation adopted in a certain population. Objective: this article rebuilds the process of congenital syphilis case definition in Brazil since 1986 up to 2004, an event that still persists as an important challenge in many countries. Methods: systematic review of technical-scientific documents about the definition of congenital syphilis cases in Brazil and in other countries. Results: this analysis subsidizes, therefore, the understanding of the current case definition, effective since January 2004, as the basis for the development of the epidemiological surveillance process. Conclusion: the importance of the appropriate case definition and revision for surveillance actions of congenital syphilis are emphasized, as well as the recognition of limits and potentialities of different modalities of epidemiological surveillance in order to generate good information to subsidize the control actions.